The yeast PRP6 gene encodes a U4/U6 small nuclear ribonucleoprotein particle (snRNP) protein, and the PRP9 gene encodes a protein required for U2 snRNP binding. - Abovich, N (1990)
PRP6 and PRP9 are two yeast genes involved in pre-mRNA splicing. Incubation at 37 degrees C of strains that carry temperature-sensitive mutations at these loci inhibits splicing, and in vivo experiments suggested that they might be involved in commitment complex formation (P. Legrain and M. Rosbash, Cell 57:573-583, 1989). To examine the specific role that the PRP6 and PRP9 products may play in splicing or pre-mRNA transport to the cytoplasm, we have characterized in vitro splicing and spliceosome assembly in extracts derived from prp6 and prp9 mutant strains. We have also characterized RNAs that are specifically immunoprecipitated with the PRP6 and PRP9 proteins. Both approaches indicate that PRP6 encodes a U4/U6 small nuclear ribonucleoprotein particle (snRNP) protein and that the PRP9 protein is required for a stable U2 snRNP-substrate interaction. The results are discussed with reference to the previously observed in vivo phenotypes of these mutants.